Pengujian Kekerasan dan Keausan Kampas Rem Sepeda Motor - Maulana Rachman; Kasda Kasda; Wardaya Wardaya; Sandi Ramahdan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study is to determine the hardness and wear of two original and local brake pads on motorcycle brakes by conducting rockwell hardness and wear tests. This test was conducted at the B4T Bandung Automotive Laboratory with results at a load of 60 Kgf, a steel ball indenter with a diameter of 1/12 inch. The results show that the average value of the local brake pad hardness level is 66.7 HR and the average value of the original brake pad is 84.93 HR proving that the highest level of hardness is found in the original brake pad. Wear testing that the original brake canvas sample initial weight 75 gr with 3 variable testing time namely test 1 around 4 minutes obtained 71 gr with eroded weight 4 gr, test 2 around 8 minutes obtained 69 gr with eroded weight 6 gr, test 3 around 12 minutes with weight 67 gr, test 3 around 12 minutes obtained 67 gr with eroded weight 8 gr local brake canvas initial weight 74 gr with 3 variable testing time namely test 1 around 4 minutes obtained 69 gr with eroded weight 5 gr, test 2 around 8 minutes obtained 60 gr eroded with eroded weight 14 gr, test 3 got 56 gr with eroded weight 18 gr, from both samples the results of wear testing that the original and local brake canvas found that the original canvas wear is harder than the local type of canvas.